Case Report: Imaging immune checkpoint inhibitor-induced yin-yang effects in the brain - Bol, K. F.; Peeters, E.; van Herpen, C. M. L.; Westdorp, H.; Aarntzen, E. H. J. G. (Frontiers in Immunology, 2023)
Background Treatment with immune checkpoint inhibitors (ICI) can induce durable responses in cancer patients, but it is commonly associated with serious immune-related side effects. Both effects are suggested to be mediated by CD8+ T-cell infiltration. Whole body CD8+ T-cell distribution can be visualized by PET imaging of a 89Zr-labeled anti-humanCD8a minibody, currently investigated in a phase 2b trial. Main body An adult patient diagnosed with metastatic melanoma developed ICI-related hypophysitis after two courses of combined immunotherapy (ipilimumab (3 mg/kg) and nivolumab (1 mg/kg) at 3 weeks interval). On a [89Zr]Zr-crefmirlimab berdoxam PET/CT scan, made 8 days before clinical symptoms occurred, increased CD8+ T-cell infiltration in the pituitary gland was detected. Simultaneously, tracer uptake in a cerebral metastasis was increased, indicating ICI-induced tumor infiltration by CD8+ T-cells. Conclusions The observations in this case report underscore the role of CD8+ T-cell in non-tumor tissues in ICI-related toxicity. In addition, it illustrates a potential role for molecular imaging by PET/CT for investigation and monitoring of ICI-induced effects.